Targeting gut microbiota to explore the Shanghuo effect of Qi-invigorating herbs - Zhao Din; Hui Cao; Yehao Zhang; Xiaoyu Zheng; Wenting Song (Elsevier, 2024)
Scope: Qi-invigorating herbs have been shown to have a tonic-like effect and to improve the body's immune system function. This study explores how high-dose Ginseng and Astragalus, two representative Qi-invigorating herbs, affect the immunes system of SD rats by regulating their gut microbiota. Method and results: We divided thirteen SD rats randomly into two groups, namely the control group and the Qi-invigorating group (Shenqi). The Shenqi rats received a mixture of Ginseng and Astragalus (Ginseng: 5 mg/kg, Astragalus: 15 mg/kg) for 28 days, once a day. After the treatment, we recorded the blood pressure and the heart rate of the rats. Metabolites of each group were detected via LC-MS, and we conducted gut microbiota profiling via 16 s rRNA sequencing. The blood pressure of the rats in the Shenqi group significantly increased compared with the control group (p<0.01), and the RGB value of the lingual picture also increased. At the genus level, we observed a higher relative abundance of Parabacteroides, Oscillibacter, and Romboutsia in the Shenqi group, and a higher relative abundance of Blautia, Subdoligranulum, and Anaerostipes in the control group. Furthermore, we also observed that the composition of the metabonomics significantly changed after the treatment of Qi-invigorating herbs. In total there were 2,862 differential metabolites (p<0.05), and we singled out 3alpha-Hydroxy-5beta-chola-7,9(11)-dien-24-oic Acid, (+)-22(29)-Hopen-6alpha-21beta-diol, 4,4'-Diapophytofluene, Cholic acid, and Wogonin as five of the most representative metabolites. Conclusions: Overall, we find that the composition and function of gut microbiota of rats in Shenqi group differed from that in the control group. Meanwhile, it can be summarized by our results that Shanghuo is related to the changes of intestinal flora and related metabolic pathways. What's more, modulating the gut microbiota and some metabolic pathways may be the mechanism by which Yiqi TCM treatment exerts its effects. Significance and impact of study: This study confirms that Shanghuo is related to disorders of energy metabolism and changes in composition and function of gut microbiota. Overdose of Qi-invigorating herbs may change the composition and function of gut microbiota and metabolism and then generate adverse effect. However, modulating the composition and function of gut microbiota and even metabolism may also be the way Qi-invigorating herbs taking effects, which needs further investigation.